Gender-Based Analysis of Social Networking: The Influence Thereof on Academic Performance of Delta State Upper Basic Social Studies Students. - Oshiogwemo, Irialuose Agatha (NIU Journal of Social Sciences, 2024)
This study looked at gender disparities in the influence of social networking on Delta State Upper Basic Social Studies students' academic performance. It used a single study question and one hypothesis to drive the use of a descriptive survey research methodology. Using stratified random sampling, 975 Basic 9 students; 481 males and 494 females were chosen for the sample. A questionnaire and Social Studies performance scores were used to gather data. The reliability of the questionnaire items was evaluated using Cronbach's alpha at a significance threshold of P<0.5. Pearson's coefficient of determination was used to answer the research question, and Pearson's Product Moment Correlation was used to test the null hypothesis at the 0.05 significance level. The finding showed a strong correlation, with gender playing a major role between Upper Basic Social Studies students' academic performance and their use of social networks. The result led to the recommendation that social networking be promoted to male and female students in Delta State Upper Basic schools in order to assist learning and improve academic achievement. Keywords:  Academic Performance , Gender, Social Networking, Social Studies.